MHD mixed convection of nanofluid in a cavity with isothermal local heater under an influence of velocity modulation of upper cold wall - Gibanov, Nikita S. (International journal of thermal sciences)
Flow and heat transfer dynamics are extremely complicated phenomena in various enclosures. The mechanism of heat transmission and its enhancement due to the presence of nanoscale particles is an important research area. Owing to the broad significance of convection fluid flows with nanoparticles in different configurations and limitations, we have addressed in this study the mixed convection of aluminum oxide (Al2O3)-water nanosuspension in a closed chamber having a moveable upper boundary and a semicircular heat source of constant temperature. The simulation has been carried out with the impacts of thermal radiation and uniform horizontal magnetic field. Mass, momentum, and energy conservation laws have been used to develop the mathematical model for assessing the effectiveness regarding the thermal performance of nanoparticles. Objective of this analysis is to study the factors that improve the effectiveness of thermal transport in heat transfer machinery and heat recovery units used in engineering and industrial processes. Firstly, appropriate transformations are employed to alter the governing system into non-dimensional forms. The dimensionless system was then numerically solved for the wide range of emerging parameters. The system of governing equations has been solved on the basis of the finite difference method. Parabolic equations have been solved using the locally one-dimensional Samarskii scheme and then using the Thomas algorithm. An elliptic equation has been approximated by central differences and then solved by the successive over-relaxation method. The obtained distributions characterize the consequences of parameters on the fluid flow, establishment time of the quasi-stationary regime, and efficiency of heat transfer in the investigated cavity. Thus, it has been revealed that the effective energy removal can be obtained for ξ = 0.01 under an influence of magnetic field and nanoparticles addition.